PERBANDINGAN CONSTRAINT INDUCED MOVEMENT THERAPY DENGAN BOBATH EXERCISE PADA EKSTREMITAS ATAS TERHADAP PENINGKATAN AKTIVITAS FUNGSIONAL INSAN PASCA STROKE - Nabila Salsabillah Warasti (Media Physiotherapy Journal of Science, 2025)
Background: Stroke is the result of one of the main disabilities in adults. Approximately 80% of people after stroke have motor disorders in the upper extremities, and 40% suffer from upper extremity dysfunction which greatly affects their ability to carry out daily activities and social participation, Objective: This study aims to determine the comparison of CIMT with bobath exercise on increasing human functional activity after stroke. Method: This research is a quasi-experiment research with a pre-test research design and post-test group design. The measurements in this study were for upper extremity functional activity, which was measured using the WMFT measuring instrument. Post-Stroke People consisted of 16 patients at the Physiotherapy Care Center Tangerang clinic. Treatment group I consisted of 8 patients with CIMT exercise intervention and treatment group II consisted of 8 patients with bobath exercise intervention. Results: The results of the examination using the WMFT before and after the intervention was given to each group were then followed by a statistical test to see the comparison of the intervention with the independent t-test in treatment group I. It was found that there was an insignificant increase in the value p value = 0.1607 or p value > 0.05, while in treatment group 2 there was also a non-significant increase with p value = 0.1175 or p value > 0.05. The results of this study indicate that administering CIMT and bobath exercise can increase functional activity which is not significant. Conclusion: There is no comparison between CIMT exercise and bobath exercise on the upper extremities in increasing human functional ability after stroke.